2005
DOI: 10.1093/alcalc/agh135
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Drunk Driving: Contribution of Alcohol Use and Related Problems, Traffic Behaviour, Personality and Platelet Monoamine Oxidase (Mao) Activity

Abstract: Our results support the notion that drunk driving is the result of a combination of various behavioural, biological and personality-related risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 25 publications
4
30
0
Order By: Relevance
“…Consistent with other research that has suggested that driver characteristics contribute to 95% of crashes (Sabey & Taylor, 1980) and that age and gender are key factors for consideration (Miaou & Lum, 1993), particularly with regard to alcohol-related crashes (Baum, 2000;Eensoo, Paaver, Harro, & Harro, 2005;Yuan, Li, & Zhang, 2013), the current study found that most of the drunk-driving offender sample were male with an average age of 33.6 years. Only 9.9% were women.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Consistent with other research that has suggested that driver characteristics contribute to 95% of crashes (Sabey & Taylor, 1980) and that age and gender are key factors for consideration (Miaou & Lum, 1993), particularly with regard to alcohol-related crashes (Baum, 2000;Eensoo, Paaver, Harro, & Harro, 2005;Yuan, Li, & Zhang, 2013), the current study found that most of the drunk-driving offender sample were male with an average age of 33.6 years. Only 9.9% were women.…”
Section: Discussionsupporting
confidence: 89%
“…Previous research on drink driving conducted in Guangxi Province, China, found that of 145 drivers who were involved in alcohol-related crashes, 99% were male with a mean age of 33.9 years (SD = 9.2) (Yuan et al, 2013). Similarly, research conducted in Australia (e.g., Baum, 2000;Eensoo et al, 2005) typically has found that there is a higher incidence of drinking and drink driving among males than females. Together, these findings suggest that the target population for further training, education, and interventions for prevention of alcohol-related driving in China should be younger males.…”
Section: Discussionmentioning
confidence: 97%
“…Previous literature has underlined the consequences of alcohol misuse during youth, including acute effects like early, unprotected sexual intercourse (Brown & Vanable, 2007;Sivaram et al, 2008), violence and antisocial behaviour (Rodney, Rodney, Crafter, & Mupier, 1999), car driving under the influence of alcohol and fatal crashes (Eenso, Paaver, Harro, & Harro, 2005;Laumon, Gadegbeku, Martin, & Biecheler, 2005), school problems such as poor academic achievement (Aertgeerts & Buntinx, 2002), grade retention (Rodney et al, 1999), school dropout (Chatterji & DeSimone, 2005) and late graduation (Renna, 2007). Previous studies also underlined long term consequences of intense alcohol use in adolescence such as strong negative developmental outcomes (Masten, Faden, Zucker, & Spear, 2008), later problematic alcohol use (Poikolainen, Tuulio-Henriksson, Aalto-Setala, Marttunen, & Lonnqvist, 2001) and which are related to later higher unemployment risks (Ellickson, Tucker, & Klein, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…We have used the database of the Estonian Psychobiological Study of Traffic Behaviour (EPSTB; Eensoo 2007;Paaver et al 2006) that includes male Caucasian subjects who drive a vehicle. NOS1 ex1f-VNTR genotype data were available for 637 random subjects (M age =35.6 years, age range 15-70 years, SD=11.2 years).…”
Section: Samplementioning
confidence: 99%
“…Participants completed four self-report impulsivity scales (Eensoo 2007;Paaver et al 2006): disinhibition and thoughtlessness as maladaptive aspects of impulsivity and excitement seeking and fast decision making as adaptive aspects of impulsivity. All four impulsivity measures were collapsed to form general impulsivity.…”
Section: Impulsivity Smoking and Agementioning
confidence: 99%